2020
DOI: 10.3390/agronomy10071005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar Application and Re-Application on Soil Bulk Density, Porosity, Saturated Hydraulic Conductivity, Water Content and Soil Water Availability in a Silty Loam Haplic Luvisol

Abstract: Due to climate change the productive agricultural sectors have started to face various challenges, such as soil drought. Biochar is studied as a promising soil amendment. We studied the effect of a former biochar application (in 2014) and re-application (in 2018) on bulk density, porosity, saturated hydraulic conductivity, soil water content and selected soil water constants at the experimental site in Dolná Malanta (Slovakia) in 2019. Biochar was applied and re-applied at the rates of 0, 10 and 20 t ha−1. Nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 61 publications
3
44
0
3
Order By: Relevance
“…This is primarily due to the solid structure of biochar, which means that its swelling capacity is much lower than SOM. An improvement of soil moisture after biochar application is partly and indirectly due to, e.g., an improvement of soil structure, as reported by Toková et al [81], but also direct effects such as biochar's capacity to retain water. Biochar, with its large surface area and a large number of micropores, alters the average surface area of the soil, pore size distribution, and, thus, the water retention capacity of the soil [82].…”
Section: Physical Properties Of Soilmentioning
confidence: 73%
“…This is primarily due to the solid structure of biochar, which means that its swelling capacity is much lower than SOM. An improvement of soil moisture after biochar application is partly and indirectly due to, e.g., an improvement of soil structure, as reported by Toková et al [81], but also direct effects such as biochar's capacity to retain water. Biochar, with its large surface area and a large number of micropores, alters the average surface area of the soil, pore size distribution, and, thus, the water retention capacity of the soil [82].…”
Section: Physical Properties Of Soilmentioning
confidence: 73%
“…Alghamdi, et al, (2020) results showed that the largest increase in both water content at field capacity and available water content was observed with the smallest biochar particle size due to increased micro-porosity as a result of the larger internal surfaces and the porous structure of the biochar particles. Toková et al, (2020) found that during the dry period, a relative increase in soil water content was observed at all biochar treatments-the largest after re-application of biochar at a dose of 20 t ha -1 at all fertilization levels. The biochar application also significantly increased plant available water.…”
Section: Introductionmentioning
confidence: 85%
“…Research on various aspects of biochar application into the soil was studied at this area. In 2018, the original plots with former biochar application were divided in halves (4x3 m) and the same biochar with the same dose (0, 10 and 20 t ha -1 ) was reapplied to one of these halves (Toková et al, 2020). In this paper we focused on impact of biochar application at the dose of 20 t ha -1 .…”
Section: Methodsmentioning
confidence: 99%